Informal labor regulations, firm boundaries, and global sourcing - Renu Bansal; Dibyendu Maiti (Asian Development Bank Institute (ADBI), 2024)
This paper extends the global sourcing model with informal labor, which spawns reputation and legal costs for violating the rules and regulations imposed on foreign firms regarding accessing informal labor under integration. Under these circumstances, foreign firms, facing a higher cost than domestic firms, prefer to outsource rather than integrate into the informal labor-abundant country under both transaction-cost and property-rights theory approaches. The attractiveness of foreign investment rises with the fall in the costs for foreign firms that access informal labor. However, such adverse effects of the cost decline with a rise in the capital intensity and bargaining strength of the foreign firm. Three sets of empirical exercises using cross-country panel data for 80 countries from 2000-2019 and pooled cross-sectional firm-level and industry-level data for 31 countries confirm such conjectures and reveal that foreign investment declines with the rise in the fraction of informal labor employed by the affiliate firm across countries, industries, and firms.
Keywords: C67; F14; F16; F21; F23; 330; global value chain; informal labor; firm boundary; labor regulations; FDI